2019
DOI: 10.2147/ijn.s224704
|View full text |Cite
|
Sign up to set email alerts
|

<p>Carrier-Free, Dual-Functional Nanorods Via Self-Assembly Of Pure Drug Molecules For Synergistic Chemo-Photodynamic Therapy</p>

Abstract: BackgroundThe combination of chemo-photodynamic therapy based on nano-technology has emerged as a preferable and promising measure for synergetic antitumor therapy.PurposeThe aim of this study was expected to overcome most of the safety concerns from nano-carriers and improve the chemo-photodynamic synergistic antitumor efficacy.MethodsHerein, we reported a facile and effective approach based on the self-assembly of chemotherapeutic agent 10-hydroxycamptothecin (HCPT) and photosensitizer chlorin e6 (Ce6) for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Unexpectedly, under rigorous, same conditions, we found that all formulations could form a uniform spherical nanostructure even if without sonication (0 min) (Figure S8), suggesting that a stronger intermolecular interaction exists between these two species to promote the coassembly easily. This coassembly of BC with Ce6 may be spontaneous with a negative Gibbs free energy change (Δ G °) similar to HCPT/Ce6 coassemblies . As the ultrasonic time extended from 0 to 8 min, BC-Ce6 NPs exhibit obviously decreased size (Figure S9), and this dimensional change after continuous ultrasound also leads to the enhanced π–π stacking in the molecular level (Figure S10).…”
Section: Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Unexpectedly, under rigorous, same conditions, we found that all formulations could form a uniform spherical nanostructure even if without sonication (0 min) (Figure S8), suggesting that a stronger intermolecular interaction exists between these two species to promote the coassembly easily. This coassembly of BC with Ce6 may be spontaneous with a negative Gibbs free energy change (Δ G °) similar to HCPT/Ce6 coassemblies . As the ultrasonic time extended from 0 to 8 min, BC-Ce6 NPs exhibit obviously decreased size (Figure S9), and this dimensional change after continuous ultrasound also leads to the enhanced π–π stacking in the molecular level (Figure S10).…”
Section: Results and Discussionmentioning
confidence: 97%
“…This coassembly of BC with Ce6 may be spontaneous with a negative Gibbs free energy change (ΔG°) similar to HCPT/ Ce6 coassemblies. 28 As the ultrasonic time extended from 0 to 8 min, BC-Ce6 NPs exhibit obviously decreased size (Figure S9), and this dimensional change after continuous ultrasound also leads to the enhanced π−π stacking in the molecular level (Figure S10). Generally, the intermolecular interactions in the supramolecular nanostructure are basically noncovalent interactions, for instance, π−π stacking, hydrogen bonding, and van der Waals forces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Additionally, because of these associative noncovalent interactions, BA-S-S and Ce6 could be assembled easily even without sonication (Figure S5), implying that this coassembly may be spontaneously similar to HCPT/Ce6 coassemblies. 37 To further visualize the coassembly and reveal the underlying possible molecular mechanism why free BA-S-S could form long lamella-like self-assemblies, while BA-S-S/Ce6 coassemblies form spherical nanoparticles, we performed a molecular dynamics (MD) simulation of a simplified model with 12 density functional theory (DFT)-optimized BA-S-S molecules and additional 3 Ce6 molecules in a water box. Initially, we investigated the possible interaction/binding of BA-S-S self-assemblies (Figure 2A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Collectively, we reasonably believe that the successful coassembly of BA-S-S with Ce6 molecules may be primarily attributed to the π–π stacking and hydrophobic interactions. Additionally, because of these associative noncovalent interactions, BA-S-S and Ce6 could be assembled easily even without sonication (Figure S5), implying that this coassembly may be spontaneously similar to HCPT/Ce6 coassemblies …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, taking advantage of the enhanced permeability and retention (EPR) effect in tumor tissues, nanoparticles (NPs) facilitate drug targeting to tumor tissues, and further influence their activities and toxic properties. 4 , 5 The investigation on nano-DDS of chemotherapeutics has been a hot topic in cancer treatments.…”
Section: Introductionmentioning
confidence: 99%